Magnetic Properties of the Amorphous Fe-Zr-B-Ni Alloys Annealed below the Crystallization Temperature - Yu, S.-C.; Lee, S.-H.; Kim, K.-S.; Rao, K.V.; Kim, K.-Y.; Kang, I.-K. (1995)
We have studied the magnetic properties of amorphous Fe83？xZr7B10Nix alloys annealed below the crystallization temperature. Such materials are considered to have a potential for high frequency core material applications because of possibilites of obtaining high effective permeability and low coercive force. The addition of Ni content of approximately 0.5？1.5 at.% was found to be effective in improving the soft magnetic properties. The temperature dependence of magnetization measured by a SQUID magnetometer are found to be in good agreement with the spin wave theory. The spectroscopic splitting g values obtained by ferromagnetic resonance(FMR) experiments increase with increasing Ni content. The values of the spin wave stiffness increases from 62.7 meV ？2 to 95.2 meV ？2 with increasing the concentration of Ni. From these experimental results, the range of the exchange interaction are deduced. ？ 1995 IEEE
Keywords: Amorphous alloys; Annealing; Coercive force; Composition effects; Crystallization; Ferromagnetic resonance; Iron alloys; Magnetic permeability; Magnetic variables measurement; Magnetization; Magnetometers; Thermal effects; Soft magnetic properties; Spectroscopic splitting values; Spin wave stiffness; Magnetic materials